Ações significativas na formação de Professores de Química inventivos através do Residência Pedagógica - SOUZA, Juliana da Silva (2024)
This present study’s address aspects based on Normative Instruction No. 05/2023 of the Pro-Rectory of Undergraduate Studies, which regulates the Course Work within the scope of the undergraduate courses of the Federal University of Pará and the Resolution of the Course Work of the Faculty of Chemistry No. 1 of 2024. In this possibility configuration, a scientific publication made in the format of an oral communication at the I North-Northeast PIBID/PRP Congress held in 2024 in the city of Salvador-Bahia will be used. That said, it is highlighted that the present research deals with the Pedagogical Residency Program (PRP), an important component in teacher training, providing the practical application of theoretical knowledge in real teaching contexts. This qualitative study, of documentary analysis, with a time frame between 2023 and 2024, aimed to reveal the contributions of the PRP in the training of Chemistry and Physics teachers, based on experiences lived by residents. Content analysis, inspired by Bardin (2011), applied to the residents' reports and guiding documents of the program, revealed three categories: (I) Regency: becoming a teacher; (II) Intervention Project in the Pedagogical Residency; and (III) Specific Activities. The results revealed that immersion in the PRP acts as a catalyst for change, promoting the development of teaching skills and the construction of an authentic professional identity. The classroom experience allowed residents to experiment with different teaching and learning methodologies, reflect critically on teaching practice, develop strategies to deal with classroom challenges, and build meaningful relationships with students and the school community. In summary, the program emerges as a unique training space, providing future Chemistry and Physics teachers with the opportunity to develop the skills necessary to act critically, reflectively, and innovatively in contemporary education.